Arctic offshore oil & gas guidelines - United States. National Oceanic and Atmospheric Administration.; Arctic Council. Protection of the Arctic Marine Environment Working Group. ([Washington, D.C.] Printed under the auspices of U.S. Dept. of Commerce, National Oceanic and Atmospheric Administration, 2002)
"October, 2002." Shipping list no.: 2003-0252-P. "These guidelines were produced by the PAME Working Group of the Arctic Council."--P. [2] of cover. At head of title: Arctic Council. Title from cover. Mode of access: Internet.